Legal aspects of technical assistance in urban landholding regularization provided for in the Brazilian Law 11888/2008 and its impact in the state of Paraíba, Brazil - Viana, George Baracuhy Cruz; Saleme, Edson Ricardo (Direito e Desenvolvimento, 2019)
This paper analyzes the role of the state in its mission of ensuring the existence of sustainable cities with adequate housing and meeting the standards set by current legal dictates. For this purpose, firstly, the right to housing guaranteed by the current Constitution, in its article 6 caput, is assessed as one of the most basic needs of the individual, considered a fundamental right since 1948 by the Universal Declaration of Human Rights. This paper also investigates the guarantee of decent housing for the citizen is effective, as provided for in the City Statute, Law No. 10257, 2001, especially with the publication of Law n. 11.888 /2008, which guarantees free public assistance in the project and construction of social housing for low-income families. This rule regulates the hiring of professionals who, while preserving their urban legislation, ensure compliance with an adequately sustainable environment. This article will use the hypothetical-deductive method and the bibliographic research methodology.